1985
DOI: 10.1111/j.1468-2958.1985.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Discussion Procedures and Decision-Making Performance.

Abstract: This study sought to obtain empirical data that either directly supports or refutes the "functional" perspective advanced by recent group decision-making theorists. Specifically, the study attempted to test the general claim that the group's satisfaction of critical task-achievement functions (or requisite conditions) is a better predictor of decision-making performance than the discussion procedures it employs in arriving at a decision. A total of 48 three-member groups were randomly assigned to one of four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
11

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 21 publications
1
56
1
11
Order By: Relevance
“…Special group process techniques like brainstorming, Delphi and the Nominal Group Technique can help to bring more structure into the discussion, which will in turn increase the group's performance as well as the commitment to a decision (White et al 1980). In that respect, the type of structure (or decision-making sequence) is of limited importance (Brilhart and Jochem 1964;Hirokawa 1985); just unthinkingly following a sequence of steps does not automatically result in a good decision (Gouran 1982;Hirokawa 1985).…”
Section: De®ciencies In Group Interactionmentioning
confidence: 97%
“…Special group process techniques like brainstorming, Delphi and the Nominal Group Technique can help to bring more structure into the discussion, which will in turn increase the group's performance as well as the commitment to a decision (White et al 1980). In that respect, the type of structure (or decision-making sequence) is of limited importance (Brilhart and Jochem 1964;Hirokawa 1985); just unthinkingly following a sequence of steps does not automatically result in a good decision (Gouran 1982;Hirokawa 1985).…”
Section: De®ciencies In Group Interactionmentioning
confidence: 97%
“…Interaction style has been shown to have a great effect on conventional teams' ability to achieve solution quality and solution acceptance on collaborative decision tasks (Hirokawa, 1985;Watson & Michaelsen 1988;Hirokawa & Gouran, 1989;Cooke & Szumal, 1994). Group y interaction styles affect communication and thus team performance by facilitating or hindering the exchange of information among group members.…”
Section: Introductionmentioning
confidence: 98%
“…Field and laboratory studies have shown the dangers of groupthink (Janis 1972;Janis and Mann (1977)) and have demonstrated that vigilance in group decision making is more important than type of decision making sequence (Brilhart and Jochem 1964;Bayless 1967;Larson 1969;Hirokawa 1985;Hirokawa and Rost 1992). One of the great advan tages of constructing causal diagrams is that it almost automatically forces the group to think critically about their problem and that it challenges hidden assumptions.…”
Section: Effective Group Faciliationmentioning
confidence: 99%